2018
DOI: 10.1186/s13044-018-0050-0
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones increase stomach goblet cell numbers and mucin expression during indomethacin induced ulcer healing in Wistar rats

Abstract: BackgroundGastric ulcers are mucosal discontinuities that may extend into the mucosa, submucosa or even deeper. They result from an imbalance between mucosal aggressors and protective mechanisms that include the mucus bicarbonate layer. Thyroid hormones have been shown to accelerate gastric ulcer healing in part by increasing the adherent mucus levels. However, the effects of thyroid hormones on goblet cell numbers and expression of neutral and acidic mucins during ulcer healing have not been investigated.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Namulema et al reported the reduction in the number of goblet cells in ethanol-exposed rats. 48 IHC staining revealed the increased expression of phospho-NF-kB p65 and COX-2 in ethanol-exposed stomach in comparison to control. While preadministration of tBHQ at both the doses significantly reduced the expression of p-NF-kB p65 and COX-2 in comparison to the ulcer group.…”
Section: Discussionmentioning
confidence: 89%
“…Namulema et al reported the reduction in the number of goblet cells in ethanol-exposed rats. 48 IHC staining revealed the increased expression of phospho-NF-kB p65 and COX-2 in ethanol-exposed stomach in comparison to control. While preadministration of tBHQ at both the doses significantly reduced the expression of p-NF-kB p65 and COX-2 in comparison to the ulcer group.…”
Section: Discussionmentioning
confidence: 89%
“…rotenone injection (2.5 mg/kg, daily) dissolved in 98% PEG-400 and 2% DMSO, 35,36 the ulcer induction was done, after an overnight fast but with access to water, using a single intragastric indomethacin (IND; Liometacen) dose by oral gavage (40 mg/kg) dissolved in distilled water. 36 Adropin Treated PD/Ulcer Group (15 Rats, Group III). Adropin 34−76 was dissolved in distilled water and administered in a dose of 2.1 μg/kg/ day (i.p.)…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…With the change in modern lifestyles, environmental pollution, and irrational use of non-steroidal anti-inflammatory drugs (NSAIDs), gastrointestinal mucosal lesions have become one of the major diseases that seriously endanger public health and social development, causing great economic and social burdens worldwide, especially in developing countries (O’Malley 2003 ; Namulema et al. 2018 ). As gastric mucosal lesion is the main pathophysiological link of gastric ulcers, gastritis, and many other gastric diseases, it is also considered by World Health Organization (WHO) as the inevitable mode of inducing gastric ulcers, chronic gastritis, atrophic gastritis, intestinal metaplasia, atypical hyperplasia, and finally developing into gastric cancer (Da et al.…”
Section: Introductionmentioning
confidence: 99%